Application of the Mind Mapping-Assisted PBL Model to Improve the Learning Outcomes of Halal and Haram Animal Fiqh in Madrasah Ibtidaiyah - Rahmawati, Septiana; Fihris, Fihris (FITK UIN Walisongo Semarang, 2024)
This research aims to improve the learning outcomes of student fiqh in halal and haram animal material through the application of the Problem Based Learning (PBL) Model supported by Mind Mapping techniques. This material often causes difficulties for students, especially in distinguishing the types of animals according to Islamic law. As a result, student learning outcomes tend to be low and often below the Minimum Completeness Criteria (KKM). To overcome this, this class action research is carried out in three cycles which include the stages of planning, implementation, observation, and reflection. Each cycle showed a significant improvement in learning outcomes. In the first cycle, student learning outcomes reached 48%, increased to 68% in the second cycle, and reached 88% in the third cycle. The use of PBL assisted by Mind Mapping has been proven to help students understand the material in a more in-depth and structured way. With this approach, students are invited to solve real problems that are relevant to daily life, so that the concepts learned are easier to understand and apply. Mind Mapping, as a visual aid, also makes it easier for students to organize information, remember, and understand concepts more systematically. The results of this study show that the application of the PBL Model assisted by Mind Mapping can be an effective learning strategy to improve fiqh learning outcomes on complex materials such as halal and haram animals.The results of the descriptive analysis of the research showed an increase in the learning outcomes of students in class VI MI Al Falah Gedongan. In cycle I (48%), cycle II (68%) and cycle III (88%). The conclusion of this study is that the application of the PBL model assisted by Mind Mapping can improve the learning outcomes of grade VI students of MI Al Falah Gedongan Baki Sukoharjo, and PBL model learning can be used as an alternative to fiqh learning